PENINGKATAN PENGETAHUAN PENGELOLAAN WISATA DI PULAU LOMBOK BERBASIS MEDIA SOSIAL BAGI SISWA KABUPATEN LOMBOK BARAT - SULAEMAN SULAEMAN; ZINNU RAIN; MA’RUF AL GIFARI; MUHAMAD SUHARDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
Social media is a communication and interaction forum used by millennials to interact and share information with one another. The potential of social media as a media for tourism promotion is very large, but it is still not optimally utilized for productive activities, including students of Madrasah Aliyah Al Madani, West Lombok Regency due to the lack of knowledge and skills of madrasah students in the use of social media they have. This training aims to improve the knowledge and creativity skills of MA Al Madani students in utilizing social media as a promotional media in tourism management, especially in program promotion activities and tourism media. The stages of this service activity process begin with observing the potential of schools, followed by discussion activities and formulating the theme of training activities in accordance with school plans and programs, then carrying out training activities according to the agreed theme until post-training evaluation activities take place. The training activities were guided by expert trainers, it was found that through this training students could develop their skills in the use of various social media as a promotional platform in developing and managing tourism programs in Lombok Nusa Tenggara. The evaluation process, by monitoring and examining the trainees' social media after one week of training, shows that the program has been successfully developed and utilized by MA Al Madani students, West Lombok Regency, West Nusa Tenggara.